Spirituality and psychiatry - Cook, Christopher C. H. 1945-; Powell, Andrew ca. 20./21. Jh (Cambridge medicine (Series), 2022)
Spirituality and Psychiatry addresses the crucial but often overlooked relevance of spirituality to mental well-being and psychiatric care. This updated and expanded second edition explores the nature of spirituality, its relationship to religion, and the reasons for its importance in clinical practice. Contributors discuss the prevention and management of illness, and the maintenance of recovery. Different chapters focus on the subspecialties of psychiatry, including psychotherapy, child and adolescent psychiatry, intellectual disability, forensic psychiatry, substance misuse, and old age psychiatry. The book provides a critical review of the literature and a response to the questions posed by researchers, service users and clinicians, concerning the importance of spirituality in mental healthcare. With contributions from psychiatrists, psychologists, psychotherapists, nurses, mental healthcare chaplains and neuroscientists, and a patient perspective, this book is an invaluable clinical handbook for anyone interested in the place of spirituality in psychiatric practice